Computing Spatiotemporal Heat Maps of Lipid Electropore Formation: A Statistical Approach - Wriggers, Willy; Castellani, Federica; Kovacs, Julio A.; Vernier, P. Thomas (Frontiers in Molecular Biosciences, 2017)
We extend the multiscale spatiotemporal heat map strategies originally developed for interpreting molecular dynamics simulations of well-structured proteins to liquids such as lipid bilayers and solvents. Our analysis informs the experimental and theoretical investigation of electroporation, that is, the externally imposed breaching of the cell membrane under the influence of an electric field of sufficient magnitude. To understand the nanoscale architecture of electroporation, we transform time domain data of the coarse-grained interaction networks of lipids and solvents into spatial heat maps of the most relevant constituent molecules. The application takes advantage of our earlier graph-based activity functions by accounting for the contact-forming and -breaking activity of the lipids in the bilayer. Our novel analysis of lipid interaction networks under periodic boundary conditions shows that the disruption of the bilayer, as measured by the breaking activity, is associated with the externally imposed pore formation. Moreover, the breaking activity can be used for statistically ranking the importance of individual lipids and solvent molecules through a bridging between fast and slow degrees of freedom. Our analysis result indicates that relatively short simulations of electroporation can provide clues about events relevant for bioelectrics experiments on much longer time scales. Our algorithms are freely disseminated with the open-source package TimeScapes.